2011
DOI: 10.1111/j.1468-3083.2011.04164.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and malondialdehyde levels in plasma and tissue of psoriasis patients

Abstract: NO and MDA levels are elevated in psoriasis patients, which may indicate that oxidative stress plays an important role in the aetiopathogenesis of psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 22 publications
0
35
0
1
Order By: Relevance
“…We also demonstrated that nitric oxide is important in the control of wound healing [10]. Nitric oxide also controls keratinocyte proliferation [11], while in human skin, it plays a key role in regulating cellular responses in diseases states such as psoriasis [12, 13], as well as to infections, heat, ultraviolet light and wounding [1416]. The aim of the present studies was to analyze the response of keratinocytes to the nitrofatty acids 9-nitrooleic acid (9-NO) and 10-nitrooleic acid (10-NO).…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that nitric oxide is important in the control of wound healing [10]. Nitric oxide also controls keratinocyte proliferation [11], while in human skin, it plays a key role in regulating cellular responses in diseases states such as psoriasis [12, 13], as well as to infections, heat, ultraviolet light and wounding [1416]. The aim of the present studies was to analyze the response of keratinocytes to the nitrofatty acids 9-nitrooleic acid (9-NO) and 10-nitrooleic acid (10-NO).…”
Section: Introductionmentioning
confidence: 99%
“…Mindezek hátterében a psoriasisos plakkokban már a betegség korai fázisában jelen lévő polimorfonukleáris fehérvérsejtek szabadgyök-terhelést okozó hatása állhat. Ezt a feltételezést erősíti az az eredmény, miszerint pozitív korreláció van a psoriasis súlyossága és az MDA koncentrációja között [19,[27][28][29].…”
Section: Malonilaldehid éS a Psoriasisunclassified
“…Though the positive outcomes associated with JYG can be observed clinically, the underlying mechanism for those outcomes is not well understood. Recent studies have suggested that nitric oxide (NO) and malondialdehyde (MDA) may play a part in the pathogenesis of various skin diseases, including psoriasis [5, 6]. Specifically, studies have shown that increased NO and MDA contribute to psoriasis activity [5].…”
Section: Introductionmentioning
confidence: 99%